2003
DOI: 10.1007/s00113-003-0573-1
|View full text |Cite
|
Sign up to set email alerts
|

Die bipolare Radiuskopfprothese bei nicht rekonstruierbaren Radiusk�pfchentr�mmerfrakturen: Indikation,Behandlung und Ergebnisse nach 5 Jahren

Abstract: The treatment of comminuted fractures of the radial head with concomitant injuries of the ulnar complex by resection of the radial head usually does not provide satisfactory long-term results. Other than joint instability in the elbow and a limited range of motion, radius proximalisation in the sense of ulnocarpal impingement, osteoarthritis and pain in the elbow have been described. Between 1995 and 1997, 11 radial head prostheses were implanted in ten patients who had sustained a comminuted fracture of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
6

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 0 publications
0
5
0
6
Order By: Relevance
“…8 The observations of Popovic et al have to be interpreted differently, as the authors presumed that only the radiolucent lines that were already visible within the first postoperative year and remained stable overtime are the result of an insufficient cementing technique, and that the progressive radiolucent lines and proximal bone resorption occur due to mechanical factors and wear debris. Because these findings were not noted in any of the numerous short-term studies, 3,12,32,34 nor in Muller's, Dotzis', or Frosch's 5-year studies, 7,9,23 nor in our 8.8-year results of Judet's bipolar radial head prosthesis, one must assume that all these radiologic findings may be the result of an initial insufficient cementing technique, perhaps worsened by mechanical factors and/or wear debris over the years.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…8 The observations of Popovic et al have to be interpreted differently, as the authors presumed that only the radiolucent lines that were already visible within the first postoperative year and remained stable overtime are the result of an insufficient cementing technique, and that the progressive radiolucent lines and proximal bone resorption occur due to mechanical factors and wear debris. Because these findings were not noted in any of the numerous short-term studies, 3,12,32,34 nor in Muller's, Dotzis', or Frosch's 5-year studies, 7,9,23 nor in our 8.8-year results of Judet's bipolar radial head prosthesis, one must assume that all these radiologic findings may be the result of an initial insufficient cementing technique, perhaps worsened by mechanical factors and/or wear debris over the years.…”
Section: Discussionmentioning
confidence: 47%
“…1,5,19,25 It has, therefore, superseded radial head resection as the treatment of choice for unreconstructable radial head fractures. 19,24,31 In many studies, encouraging short-term results have been reported for monobloc as well as bipolar implants 3,[7][8][9]12,17,18,21,23,27,32,34 ; but, there still exists a lack of information concerning long-term results.…”
Section: Discussionmentioning
confidence: 96%
“…) Several studies have shown good short-to midterm results of metal radial head prostheses. 1,4,6,7,8,10,11,15,18,19,28,31 However, only scarce data are available for their long-term outcome. 9 There is concern about the potential for long-term cartilage wear.…”
mentioning
confidence: 99%
“…8 Eine 74-jährige Patientin, bei der es nach Ellenbogenluxation und Radiuskopfresektion mit ulnar-und radialseitiger Bandnaht zur wiederholten Luxation kam und der wir die Prothese sekundär am 62. Tag nach dem Unfall implantierten, erzielte subjektiv und funktionell ein befriedigendes Ergebnis.…”
Section: Introductionunclassified
“…Das Patientenkollektiv zeigte weder ein andauerndes Instabilitätsgefühl noch einen Cubitus valgus, eine Demineralisierung, eine Arthrose am Capitulum humeri oder Beschwerden im Handgelenk. Während der Einsatz bei Begleitverletzungen wie ulnarer Bandinstabilität und/oder Frakturen (Mason IV) anerkannt ist [8,9], sehen wir -wie Judet et al [12] -aufgrund der sehr guten und guten subjektiven Ergebnisse sowie der niedrigen intra-und postoperativen Komplikationsrate darü-ber hinaus die Indikation zur Implantation bei Monoverletzungen des Speichenkopfs (Mason III). …”
unclassified